Apnea Threshold in Pediatric Brain Death: A Case with Variable Results Across Serial Examinations - Sosa, Tina; Berrens, Zachary; Conway, Susan; Stalets, Erika L. (Journal of Pediatric Intensive Care, 2019)
Consensus guidelines currently exist for the evaluation of pediatric patients with suspected brain death. The guidelines include the requirement for two consistent examinations separated by an observation period and a threshold of 60 mm Hg for PaCO2 during apnea testing. We present a patient who met all prerequisites to perform brain death examination but had variability in examinations during apnea testing. We discuss our strategy in managing these unexpected findings, including the importance of open and ongoing communication with the family, and the implications for current guidelines for the determination of brain death in pediatric patients.
Keywords: Pediatric; brain death; apnea